Analysis of rod-cone dystrophy genes reveals unique mutational patterns. Issue 1 (13th December 2022) - Jaffal, Lama; Ibrahim, Mariam; El Shamieh, Said
Abstract : Background: Rod-cone dystrophy (RCD) is the most common inherited retinal disease that is characterised by the progressive degeneration of retinal photoreceptors. RCD genes classification is based exclusively on gene mutations' prevalence and does not consider the implication of the same gene in different phenotypes. Therefore, we first investigated the mutations occurrence in autosomal recessive RCD (arRCD) and non-arRCD conditions. Then, finally, we identified arRCD enriched mutational patterns in specific genes and coding exons. Methods and results: The mutations patterns differed according to arRCD (p=0.001). Specifically, When compared with missense; insertions/deletions (OR=1.2, p=0.007), nonsense (OR=1.2, p=0.014) and splice-site mutations (OR=1.6, p=0.038) increased the OR of arRCD by 20%–60% versus non-arRCD conditions. The gene-based analysis identified that EYS, IMPG2, RP1L1 and USH2A mutations were enriched in arRCD (p<0.05). The exon-based analysis revealed specific mutation patterns in exons of CRB1, RP1L1 and exons 12, 60 and 62 coding for Lamin EGF and FTIII domains of USH2A . Conclusion: The current analysis showed that many aRCD genes have unique mutational patterns.